Advocacy in Ideas: Legal Education and Social Movements - Bell, Monica; Hernández, Tanya K.; Maldonado, Solangel; Perkins, Rachelle; Thomas, Chantal; Johnson, Olantude; Lopez, Elise (Columbia Journal of Gender and Law, 2018)
Panel moderated by Professor Olatunde Johnson, featuring Professors Monica Bell, Tanya K. Hernández, Solangel Maldonado, and Chantal Thomas. Introduced by Elise Lopez.